THE LEGAL ANALYSIS OF “TEORI KEDAULATAN NUSANTARA” TOWARDS THE NEW CONCEPTION OF INDONESIA AIRSPACE SOVEREIGNTY - Kusumaningrum, Adi (Indonesian Journal of International Law, 2017)
Art. 1 Chicago Convention of 1944 confirms that every state has a complete and exclusive sovereignty over the airspace above its territory. This arrangement gives the highest role of state in controlling air transportation based on state sovereignty principles. The concept of airspace sovereignty faced challenges with the introduction of international air transportation liberalization through deregulation provisions. Such liberalization policy is later known as ‘open sky policy’. Such open sky policy includes the establishment of single market such as Single European Sky dan ASEAN Single Aviation Market. The liberalization led to a situation where sovereignty concept has been regarded from a different perspective. It is widely argued that the smooth operation of new forms of international cooperation requires a more flexible perception of sovereignty. This study wants to analyze the concept of Indonesia airspace sovereignty. A theory of Indonesia airspace sovereignty that ever born is the "Teori Kedaulatan Nusantara" by Priyatna Abdurrasyid in the 1970s. "Teori Kedaulatan Nusantara" based on two doctrines i.e. the doctrine of necessity and doctrine of right of self-preservation that is the core of military/security aspect. In the other hand, what has become clear in the last few decades is that the economic aspects of airspace sovereignty have dominated change. This paper argues that there is a continuing trend away from the absolute airspace sovereignty regime towards something less. It is submitted that preservation theory cannot be sustained in the Indonesia airspace sovereignty doctrine. This paper asserts that the new paradigm of international air transport drives Indonesia towards the release of some aspects of Indonesia’s airspace sovereignty doctrine.